PUBLIC SPEAKING AND DIGITAL MARKETING TRAINING TO IMPROVE THE QUALITY AND COMPETITIVENESS OF HUMAN RESOURCE CANDIDATES FOR THE DAYAH BABUL HUDA SANTRI, COT SUWE HAMLET, PADANG SAKTI VILLAGE, MUARA SATU DISTRICT, LHOKSEUMAWE CITY - Ratna; Darmawati Muchtar; Syarifah Safira; Hijri Juliansyah; Mariyudi; Ichsan; Devi Andriyani (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Language is a key medium for communication and has a significant impact on human development. Inability to communicate can lead to a lack of confidence and fear, particularly in public speaking, which is ranked as a more common fear than even heights. This highlights the importance of public speaking as a skill that, without practice, can cause psychological challenges in those unfamiliar with it. Hence, public speaking training is crucial to helping teenagers develop their potential. In addition to communication skills, teenagers need to be aware of the competitive job market and the importance of mastering technology. In Aceh, high unemployment and poverty rates are partly due to the workforce's lack of entrepreneurial skills and low interest in business, worsened by negative societal views on young entrepreneurs still in school. Most businesses run by young people still use outdated methods, even though smartphones, as tools for modern business, are widely available. However, smartphones are often used unproductively for gaming, social media, or online shopping instead of more beneficial uses like digital marketing. Entrepreneurship education and economic independence should be introduced early to foster responsibility and entrepreneurial spirit in youth. Encouraging creative thinking and proper smartphone use can help generate additional income. To address these issues, public speaking and digital marketing training was provided at Dayah Babul Huda, with students and teachers as partners. The goal is to shift their mindset for a better future, producing young individuals capable of communication and innovation. The training, held on July 26-27, 2024, was attended by 40 students and 10 teachers. Results were very positive, with 95% recognizing the importance of public speaking and digital marketing and 85% able to practice these skills effectively.